Association of HIV Suppression With Kidney Disease Progression Among HIV-Positive African Americans With Biopsy-Proven Classic FSGS. (15th December 2018) - McMahon, Blaithin A.; Hanouneh, Mohamad; Chedid, Alice; Fine, Derek M.; Chen, Teresa K.; Foy, Matthew; Lucas, Gregory M.; Estrella, Michelle M.; Atta, Mohamed G.
Abstract : Background: In the era of combined antiretroviral therapy, classic focal segmental glomerulosclerosis (FSGS) is the most common histopathological finding in African American HIV-positive patients with kidney disease. We sought to determine whether HIV suppression is associated with lower risk of progression to end-stage renal disease (ESRD) among HIV-positive African Americans with biopsy-confirmed classic FSGS. Methods: HIV-positive African Americans who underwent kidney biopsies at a single tertiary hospital between January 1996 and June 2011 were confirmed as having classic FSGS by the presence of segmental glomerulosclerosis without features of HIV-associated nephropathy. Multivariable Cox proportional hazards models were used to examine the independent association of viral suppression (HIV-RNA < 400 copies per milliliter at biopsy) with time to progression to ESRD. Results: Of the 55 HIV-positive African Americans with classic FSGS, 26 had suppressed viral loads at the time of biopsy. Compared to viremic patients, those who were virally suppressed had a significantly higher mean CD4 + cell count (452 vs. 260 cell/mm 3, respectively; P = 0.02) and median estimated glomerular filtration rate (53.5 vs 35.5 mL/min/1.73 m 2, respectively; P = 0.002). Adjusting for sex and baseline CD4 + cell count, estimated glomerular filtration rate, and proteinuria, those with HIV-RNA levels <400 copies per milliliter at baseline had a 75% lower risk of progressing to ESRD (hazard ratio = 0.25; 95% CI: 0.07 to 0.88) during a median follow-up time of 2.70 years (interquartile range: 0.80–5.15 years). Conclusions: HIV suppression is associated with significantly lower risk of progression to ESRD among HIV-infected African Americans with classic FSGS, supporting the potential role of combined antiretroviral therapy for this histopathology in addition to HIV-associated nephropathy among HIV-positive individuals.